DISNEY PRINCESS SEQUELS IN THE PERSPECTIVE OF SECOND WAVE FEMINISM IN AMERICA - Astrinda N. Iswalono; Listiyanti Jaya Arum (Rubikon : Journal of Transnational American Studies, 2021)
Disney Animation Production, one of the media manifesting American sociology phenomena, discovered a breakthrough by depicting Princess movies. Starting with the appearance of Snow White (1937), followed by Cinderella (1950) and other sequels of Princess movies, Disney reflected one important progress of American history. The development of the sequels was estimated to be under the appeal of the Second Wave Feminism movement. Hypothesizing the change was within American society, a gender study by Nancy Hewitt would direct the observation of the study. The First Period Princesses (1937-1959) reflected the idea of the American Golden Age, also where the recognition of the role of women in wider society began. Meanwhile, the Second Period (1989-2009) claimed the social acceptance of public access by glorifying unique characters from women. The Princesses in the Third Period (2009-2014) were able to attest their own power in order to broaden the horizon of gender equality and equity.